A Protozoology and Parasitological Techniques Brochure - Josefina Isabel Vázquez Martínez; Miladys Caridad Cedeño Borges; Mabel Collazo Díaz; Martina Sabina Jiménez Suárez; Luis Quintero Hernández; Jorge Barleta Del Castillo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2012)
Parasites are a health problem worldwide. Thier control is a prime target of the World Health Organization so that it becomes necessary for students, technicians and professionals in microbiology to be updated in parasitological technical procedures, which are scattered in several sources but not included in the basic literature. It becomes necessary to compile them all into a single text that allows the active search of information. The aim of this brochure is to provide a system of techniques and procedures to facilitate the identification and diagnosis of human parasitic diseases in the laboratories of Primary and Secondary Health. Concepts and procedures within the field of study are included and it contains also a contents outline which summarizes their essence. The theoretical contents listed in this brochure were developed in response to the contents included in the program for biological agents incorporated to the new curriculum of Bachelors in Health Technology, Bachelors in Clinical Bio-analysis and the rest of the studies in the field of Medical Sciences.